Genetic analysis of pyramided genes for resistance to bacterial blight (Xanthomonas oryza pv oryzae) and development of resistant lines of basmati rice ((Oryzae sativa) - Satya, P; Singh, V P; Singh, A K (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during 2000-2003 to study segregation pattern of 4 pyramided resistance genes against bacterial blight caused by Xanthomonas oryza pv oryzae ’IRBB 60’ in crosses involving 3 susceptible basmati quality genotypes (’Pusa Basmati 1’, ’Pusa 1121’ and ’Pusa 1387’) of rice (Oryza sativa L.). All the basmati quality genotypes were found susceptible to bacterial blight. Three genes, Xa 4, xa 13 and Xa 21 were found resistant, while xa 5 showed susceptible reaction. Genetic analysis of ’IRBB 60’ indicated 2 dominant and 1 recessive gene controlling resistance against bacterial blight in the cross ’Pusa Basmati 1’ x ’IRBB 60’ and ’Pusa P 1121’ x ’IRBB 60’. Deviation from expected segregation was observed in ’Pusa 1387’ x ’IRBB 60’ cross that may be owing to residual level of resistance or epistatic interaction. From the segregating generations, 32 high-quality, high resistance lines were identified that possessed high linear kernel elongation and length/breadth ratio.